2002
DOI: 10.1046/j.1365-2265.2002.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antihypertensive medication on aldosterone and renin concentration in the differential diagnosis of essential hypertension and primary aldosteronism

Abstract: Beta-blockers and aldosterone antagonists have the strongest impact on the renin-angiotensin system. The decrease in renin concentration by beta-blockers leads to an increase in the ratio of aldosterone to renin, and thus to false-positive results in patients with essential hypertension. Calcium channel blockers, and probably also ACE inhibitors and AT1 receptor antagonists alone or in combination, may be continued during screening for primary aldosteronism by determination of renin and aldosterone concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 40 publications
5
95
1
11
Order By: Relevance
“…11,13,34,35 The results of this study match well with the data of previously published studies showing that treatment with ACEI or ARB was associated with higher renin concentrations and a lower ARR. 9,17,36 Of note, the effects were more profound in patients with EH. Accordingly, the SUSPPUP ratio was less influenced by treatment with ACEI or ARB in PA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…11,13,34,35 The results of this study match well with the data of previously published studies showing that treatment with ACEI or ARB was associated with higher renin concentrations and a lower ARR. 9,17,36 Of note, the effects were more profound in patients with EH. Accordingly, the SUSPPUP ratio was less influenced by treatment with ACEI or ARB in PA.…”
Section: Discussionmentioning
confidence: 96%
“…However, the A PL /PRA ratio is influenced by numerous factors and sampling conditions, including age, sodium intake, time of day when the samples are collected, posture, serum potassium concentration, kidney function and medication. [9][10][11][12] Other studies indicated that A PL /PRA is a valid screening test also in patients with ongoing antihypertensive treatment. 13 As many factors affect the A PL /PRA, it was recommended as a screening test only and it should be repeated if initial results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…ALD antagonists were discontinued at least 6 weeks before the investigation; angiotensin converting enzyme (ACE) inhibitors and Ang II receptor blockers were discontinued 4 weeks before; β-blockers, dihydropyridine-type calcium antagonists and clonidine were progressively reduced and withdrawn 2 weeks before. α1-Blockers and slow-release forms of verapamil, which have a lesser effect on the ARR (29,30) were withdrawn 1 week before. Medications that might interfere with the renin-ALD axis, such as steroids, sex hormones, liquorice or non-steroidal anti-inflammatory drugs were also withheld for at least 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, alguns investigadores acreditam que valores muito elevados dessa relação seriam suficientes para o diagnóstico definitivo (14). Um ponto que deve ser levado em consideração na interpretação da relação A/ARP é que vários medicamentos podem interferir na sua acurácia (15,16). Assim, beta-bloqueadores elevam a relação e a maioria dos outros agentes hipotensores (diuréticos, inibidores da ECA e de receptores de angiotensina, bloqueadores de canais de cálcio, bloqueadores de receptores alfa-adrenérgicos) a diminuem e, portanto, podem interferir na interpretação dos resultados.…”
Section: Discussionunclassified